2020
DOI: 10.3389/fcell.2020.00008
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Interactome: A Focus on Antiviral Signaling Pathways

Abstract: In the last years, proteomics has represented a valuable approach to elucidate key aspects in the regulation of type I/III interferons (IFNs) and autophagy, two main processes involved in the response to viral infection, to unveil the molecular strategies that viruses have evolved to counteract these processes. Besides their main metabolic roles, mitochondria are well recognized as pivotal organelles in controlling signaling pathways essential to restrain viral infections. In particular, a major role in antivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
86
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 144 publications
0
86
0
Order By: Relevance
“…Our previous work established that platelets could release mitochondria contributing to the immune modulation and islet b-cell regeneration [13]. To explore the mitochondrial function in viral infection, flow cytometry indicated that while the purified platelet-derived mitochondria did not express ACE2 (Figures 3D), they strongly display the mitochondrial antiviral-signaling protein (MAVS) with the percentage of MitoTracker Red + HSP60 + MAVS + mitochondria at 96.02% ± 2.74% ( Figure 3E, n = 3) [21]. This data suggests that platelets may have potential to improve antiviral immunity through the releasing mitochondria.…”
Section: No Expression Of Ace2 On Plateletsmentioning
confidence: 99%
“…Our previous work established that platelets could release mitochondria contributing to the immune modulation and islet b-cell regeneration [13]. To explore the mitochondrial function in viral infection, flow cytometry indicated that while the purified platelet-derived mitochondria did not express ACE2 (Figures 3D), they strongly display the mitochondrial antiviral-signaling protein (MAVS) with the percentage of MitoTracker Red + HSP60 + MAVS + mitochondria at 96.02% ± 2.74% ( Figure 3E, n = 3) [21]. This data suggests that platelets may have potential to improve antiviral immunity through the releasing mitochondria.…”
Section: No Expression Of Ace2 On Plateletsmentioning
confidence: 99%
“…For example, mitochondria controls cell cycle ( Antico Arciuch et al, 2012 ), cellular differentiation ( Papa et al, 2019 ), signal transduction ( Bohovych and Khalimonchuk, 2016 ), cell metabolism ( Spinelli and Haigis, 2018 ), and apoptosis ( Wang and Youle, 2009 ). In addition, mitochondria serve as an anti-viral signaling platform by activating immune responses through MAVS (mitochondrial antiviral signaling) ( Seth et al, 2005 ; Jacobs and Coyne, 2013 ; Refolo et al, 2020 ) and initiating cell death ( Lei et al, 2009 ). It is therefore not surprising that viruses target mitochondria to promote viral replication ( Chatel-Chaix et al, 2016 ; Barbier et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some viral proteins have been shown to interact with MAVS proteins and dampen their activity. Viral proteases can also cleave MAVS ( 144 ). Recently, miR-22 was found to inhibit MAVS expression at the RNA level ( 145 ).…”
Section: Viral Manipulation Of Autophagy-dependent Regulation Of Innamentioning
confidence: 99%